Bridging the Innovation Gap for Sustainable Development : Romania’s Position in the European Innovation Ecosystem - Cramariuc, Otilia; Pașcu , Paul; Popescu , Mihai (Journal of Economic Development, Environment and People, 2025)
Background: Romania remains the EU’s lowest-performing country in innovation, classified as an “emerging innovator” in the European Innovation Scoreboard. This paper explores the sustainability implications of this innovation gap by assessing Romania’s position within the EU innovation ecosystem. Methods: Using a mixed-methods approach, the study combines quantitative analysis of key indicators—such as R&D intensity, intellectual property output, digitalization, and entrepreneurial activity—with qualitative evaluation of policy documents and institutional frameworks. Results: The results reveal persistent structural deficiencies, including chronic underinvestment in research and development, weak university-industry collaboration, and limited innovation commercialization. While Romania has made progress in digital infrastructure—achieving broadband penetration above the EU average—and improved some aspects of research quality, these advances are undermined by declining public R&D funding, low venture capital availability, and high brain drain. The findings suggest that Romania’s innovation gap poses significant challenges to achieving sustainable economic growth and alignment with the 2030 Sustainable Development Goals, particularly SDG 8 (Decent Work and Economic Growth) and SDG 9 (Industry, Innovation and Infrastructure). Closing this gap will require integrated policy reforms, long-term investment strategies, and institutional modernization. Conclusions: The paper concludes that fostering a stronger innovation ecosystem is essential for enhancing Romania’s competitiveness, resilience, and sustainable development trajectory within the EU.